Early Phase Psychiatric Response for Children and Adolescents After Mass Trauma: Lessons Learned From the Truck-Ramming Attack in Nice on July 14th, 2016 - Askenazy, Florence; Gindt, Morgane; Chauvelin, Lucie; Battista, Michèle; Guenolé, Fabian; Thümmler, Susanne (Frontiers in Psychiatry, 2019)
Recent years have seen a multiplication of terrorist attacks in public places across European and North American countries, thus heightening the need for public mental health planning and response strategies focused on the special needs of children and their families. The present article retrospectively analyzes the early phase psychiatric response for children and adolescents after the truck attack in Nice on July 14th, 2016. In addition, lessons which can be drawn from it will be discussed, with a focus on organizational challenges in the early phase. During the first two weeks after the attack, 668 individuals have been registered at the medico-psychological emergency unit of the Children’s Hospitals of Nice, including 365 (54.6%) children and adolescents of all ages. Overall, 146 child and adolescent mental health care professionals participated to in this specific deviceprotocol, including 75 psychiatrists and psychologists. The implementation of the medico-psychological emergency unit dedicated to the pediatric population has been an indispensable and unprecedented public health challenge in our country. Future studies are needed in order to evaluate and to improve the efficiency of the individual as well as collective impact of early phase psychiatric interventions dedicated for children and adolescents after mass trauma.